Micropropagation of medicinal herb, Hypochaeris radicata L. via indirect organogenesis. - Senguttuvan, Jamuna; Subramaniam, Paulsamy (Research in Biotechnology, 2014)
Hypochaeris radicata is a perennial herb, commonly called as Ã¢â‚¬Ëœhairy catÃ¢â‚¬â„¢s-earÃ¢â‚¬â„¢. The edible leaves and juice form of roots are suggested by the local healers of Nilgiris, Tamil Nadu, India for the treatment of inflammation and infectious diseases and for other health benefits. They were exploiting this plant severely, for the preparation of herbal formulations. Ã‚Â The present study was aimed at to establish the H. radicata through in vitro cultures using in vitro derived leaf explants for conservation of this species in natural habitat. Effective callus formation was noted in the MS medium fortified with BAP and NAA at 3.0 and 1.0 mg/L respectively (98.83%) followed by BAP and NAA at 3.0 and 0.5mg/L respectively (93.33%) and 2,4-D at 0.2mg/L (96.36%). The colour of the callus was yellowish green produced in MS medium with BAP and NAA and pale yellow in 2,4-D. The in vitro derived calli were well responded for shoot formation (94.25%) and root (87.65%) formations in BAP and NAA at 3.0 and 1.0mg/L respectively. The in vitro regenerated plantlets were successfully acclimatized (72.54%) in the hardening medium containing garden soil: sand: vermicompost of 1:1:1 by volume. The described protocol could be useful for germplasm conservation and commercial cultivation of H. radicata.